Emocjonalizm czy symbolizm Norwida? Dyskusja z ujęciem liryki autora Vade-mecum przez Danutę Zamącińską - Rzońca, Wiesław (Poznańskie Studia Polonistyczne. Seria Literacka, 2009)
The polemical article addresses and questions the findings and determinations given by Zamącińska, who treats Norwid’s poetry as heavily marked emotionally which, according to the literary researcher and scholar, is decisive in assigning the poet to the generation of Romantics. Questioning the arguments given by Zamącińska, the present author points at a considerable decrease in individualism and direct expression in the writings of Norwid in favour of the so-called “quidamization”, i.e. a forming process of underdetermined man and “one of the may”. Concurrently, emotions find their way to the poetical image co-created by the description in which general notions constitute a substantial component. The poetics of conditionality, sensitivity to the changeability of the world and the momentous character of reality, and at the same time sensitivity to light, sphericity and multicolourness of poetical space are decisive in attributing the artistic workshop of Norwid to the aesthetics of the second half of the nineteenth century.